Advanced process control in laser-based powder bed fusion–Smart Fusion feedback-loop control as a path to uniform properties for complex structures? - Florian Nahr; Tobias Novotny; Dominik Kunz; Ulrich Kleinhans; Lova Chechik; Dominic Bartels; Michael Schmidt (Journal of Materials Research and Technology)
Laser-based powder bed fusion of metals (PBF-LB/M) enables the production of complex parts with high freedom of design. However, changes in cross-sectional area with build height influence inter-layer times and heat dissipation, resulting in potential local overheating. Since the temperature affects the microstructure and material properties, controlling the thermal history is necessary. To achieve this, a dynamic adjustment of energy input in response to the thermal conditions is required. Smart Fusion feedback-loop control monitors gray values recorded by optical tomography and compares them to a material and process specific target. If any deviations are identified, the system corrects them by applying locally varied laser power in the next layer. This study investigates the impact of the feedback-loop control on the microstructure evolution of titanium alloy Ti6Al4V and maraging steel MS1. Cuboids and complex parts with heat-accumulating features were manufactured using feedback-loop control and directly compared to their open-loop counterparts. Gray value profiles of the open-loop complex parts revealed large variations in temperature and geometry dependent differences in microstructure. The Smart Fusion feedback-loop control lead to a more constant temperature profile. In Ti6Al4V, this made the microstructure go from tempered martensite in the bulk section of the open-loop part to a consistent acicular martensitic structure in the feedback-loop controlled part. In MS1, the open-loop lead to signs of in-situ precipitation resulting in a significant local hardness increase in comparison to the feedback-loop control. Finally, the complex MS1 part could be built without minimum exposure times and uniform hardness of 350 HV0.5.